Not Just Any Village: Lifestyle Migration and the Search for Cultural Compatibility in Turkey's Gallipoli Peninsula - Erkan Öcek, Rüya; Islam, Tolga (European Journal of Geography, 2025)
This article examines the motivations and destination choices of urban residents relocating to rural areas in Turkey’s Gallipoli Peninsula, a “late-discovered” region that has recently attracted a growing number of lifestyle migrants. Drawing on qualitative fieldwork—including in-depth interviews and participant observation in seven villages—the study analyzes how migration decisions emerge through the interaction of urban disillusionment and rural attraction. Employing Lee’s (1966) push-pull framework within the broader literature on lifestyle migration, it demonstrates that these relocations are not isolated acts of individual preference but socially embedded and morally charged projects of self-realization. The peninsula’s appeal stems from its perceived authenticity as an "undiscovered" destination, largely untouched by the over-commercialization. This “quest for authenticity,” however, operates through culturally specific moral geographies: migrants are not simply searching for rural authenticity but specifically seeking progressive rural spaces that can accommodate their secular, liberal lifestyles—what they describe as "open-minded" and "democratic" environments distinct from "conservative Anatolia." Their rejection of over-commercialized destinations while simultaneously avoiding "conservative" rural areas reveals a narrow corridor of acceptable rurality defined by both authenticity and cultural comfort. By highlighting how lifestyle migration in Turkey operates through an additional cultural-compatibility filter, this study extends existing debates on lifestyle migration and demonstrates that the notion of a “better life” is deeply contingent upon cultural and political contexts. Furthermore, the study carries early warning signs that the migrants' presence may trigger rural gentrification processes similar to those observed in other amenity-rich regions across Turkey. Highlights: Cultural compatibility filter shapes rural relocation choices beyond amenities. Migrants seek "authentic yet progressive" rural spaces in Gallipoli Peninsula. Early signs show Gallipoli’s “authentic” villages facing rural gentrification risks.